Indirect frequency estimation based on second-order adaptive FIR notch filter - Punchalard, R.; Koseeyaporn, J.; Wardkein, P. (My University, 2009)
This paper deals with estimating the frequency of sinusoidal signal buried in broad band noise. The simple unbiased indirect frequency estimation (IFE) algorithm is proposed for a second-order adaptive finite impulse response (FIR) notch filter with constrained zeros. The technique of estimating input noise variance is employed to remove the bias existing in the estimated filter parameter. Also, the difference equation for the convergence of the expectation of the estimated parameter and the closed-form of steady state estimation mean square error (MSE) are derived. In addition, extensive simulations are conducted to corroborate the efficiency of the proposed estimator with the theoretical analysis. © 2009 Elsevier B.V. All rights reserved.
Keywords: Adaptive FIR notch filter; Indirect frequency estimation; Unbiased estimator